1992
DOI: 10.1073/pnas.89.5.1562
|View full text |Cite
|
Sign up to set email alerts
|

Global control in Pseudomonas fluorescens mediating antibiotic synthesis and suppression of black root rot of tobacco.

Abstract: Pseudomonas fluorescens CHA0 colonizes plant roots, produces several secondary metabolites in stationary growth phase, and suppresses a number of plant diseases, including Thielaviopsis basicola-induced black root rot of tobacco. We discovered that mutations in a P. fluorescens gene named gacA (for global antibiotic and cyanide control) pleiotropically block the production of the secondary metabolites 2,4-diacetylphloroglucinol (Phl), HCN, and pyoluteorin. The gacA mutants of strain CHA0 have a drastically red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
318
1
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(325 citation statements)
references
References 30 publications
4
318
1
2
Order By: Relevance
“…After cycling seedlings in previously cropped soils (cycles 5 through 8), two trends were noticed in the characteristics of populations of fluorescent Pseudomonas spp. Firstly, there appeared to be an overall increase in HCN producers (Table 1); although HCN may be involved in suppression of plant diseases (Laville et al 1992), production by rhizobacteria also can have a detrimental effect on some plants (Bakker and Schippers 1987). Secondly, throughout the course of these cycling experiments, there appeared to be an overall decline in the number of Phl isolates (Table 1), especially noticeable in cycles 5 through 8.…”
Section: Discussionmentioning
confidence: 99%
“…After cycling seedlings in previously cropped soils (cycles 5 through 8), two trends were noticed in the characteristics of populations of fluorescent Pseudomonas spp. Firstly, there appeared to be an overall increase in HCN producers (Table 1); although HCN may be involved in suppression of plant diseases (Laville et al 1992), production by rhizobacteria also can have a detrimental effect on some plants (Bakker and Schippers 1987). Secondly, throughout the course of these cycling experiments, there appeared to be an overall decline in the number of Phl isolates (Table 1), especially noticeable in cycles 5 through 8.…”
Section: Discussionmentioning
confidence: 99%
“…For construction of a GacA ¹ Pvd ¹ double mutant of CHA0 from the Pvd ¹ strain CHA400, a gacA'::' lacZ fusion was used instead of the kanamycinresistance cartridge previously proposed by Laville et al (1992), since strain CHA400 already carries a kanamycin-resistance determinant (on Tn1733). Triparental matings were performed in two steps, as described previously (Voisard et al, 1988.…”
Section: Bacterial Matings and Construction Of P Fluorescens Mutantsmentioning
confidence: 99%
“…Recent reports revealed that besides environmental factors and its autoregulation (Abbas et al, 2002;Duffy & Defago, 1999;Schnider-Keel et al, 2000), the production of 2,4-DAPG is regulated by a series of transcriptional and translational factors, including the repressor PhlF (Delany et al, 2000;Haas et al, 2000), the two-component regulatory system GacS/GacA (Haas & Défago, 2005;Laville et al, 1992), regulatory PrrB (Aarons et al, 2000) and RsmY (Valverde et al, 2003) RNA, global regulator proteins MvaT and MvaV (Baehler et al, 2006) and disulfide interchange protein DsbA (Mavrodi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%